Improving the perceived high workload of employees in consumer segments department of a trust company - Malubay, Maria Angelica (Animo Repository, 2023)
This action research intended to address the issue of perceived high workload of employees under the Consumer Segments Department of a Trust Company. Our department has been experiencing high volumes of workload which causes work stress and blurring of work-life balance on most employees. Poor time and workload management skills are the major factors causing our current problem. In Cycle 1 of the action research, our intervention was to establish workload/task management initiative within our team by using the Kanban Board approach. We conducted a post-assessment survey which showed some favorable results. In Cycle 2 of this action research, we improved the workload management by classifying priority tasks through applying the Eisenhower Matrix in the Kanban Board. We conducted another post-assessment survey which showed that our interventions yielded much better results. We also learned that the level of self-management, social support, role ambiguity and task complexity, if guided by appropriate workload/task management tools, will help in determining the perceived workload of an employee and improve their job performance in general. Keywords: workload management, perceived workload, Kanban Board, Eisenhower Matrix